2019
DOI: 10.1101/790261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Minimal Residual Disease in Acute Myeloid Leukemia through Stochastic Modeling of Clonality

Abstract: Event-free and overall survival remains poor for acute myeloid leukemia (AML). Chemoresistant clones contributing to relapse of the disease arise from minimal residual disease (MRD) rather than resulting from newly acquired mutations during or after chemotherapy.MRD is the presence of measurable leukemic cells using non-morphologic assays. It is considered a strong predictor of relapse. The dynamics of clones comprising MRD is poorly understood and is considered influenced by a form of Darwinian selection. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Fluctuations also become less meaningful when the value of K increases, since the noise increases by the square root of cell the number and, therefore, for long periods of time, it fluctuates on a scale of ffiffiffi ffi K p . This model behavior could be useful to characterize the minimal residual disease (MRD) and how it can develop into the complete cure of the patient or into a relapse, as demonstrated in [41], where the authors showed how random events in MRD may affect the patient's fate. This work may aid clinicians in choosing treatment strategies that reduce the risk of relapse.…”
Section: Trends Trends In In Pharmacological Pharmacological Sciences Sciencesmentioning
confidence: 99%
“…Fluctuations also become less meaningful when the value of K increases, since the noise increases by the square root of cell the number and, therefore, for long periods of time, it fluctuates on a scale of ffiffiffi ffi K p . This model behavior could be useful to characterize the minimal residual disease (MRD) and how it can develop into the complete cure of the patient or into a relapse, as demonstrated in [41], where the authors showed how random events in MRD may affect the patient's fate. This work may aid clinicians in choosing treatment strategies that reduce the risk of relapse.…”
Section: Trends Trends In In Pharmacological Pharmacological Sciences Sciencesmentioning
confidence: 99%